Memory, Language, and the Making of Truth: Towards an Hermeneutic of Augustine’s Conversion Narrative - Cvetković, Carmen Angela 19XX- (Augustinianum, 2015)
For over a century modern scholars have passionately debated whether Augustine’s conversion narrative from Confessions 8 is an accurate description of what ‘has really happened’ in 386 in a garden in Milan without reaching so far a consensus. However, long before modern scholars disputed the historicity of his conversion account Augustine was already confronted with the mistrust of his contemporaries who doubted the authenticity of his conversion and compelled to deal with their accusations. This article intends to show how in the Confessions Augustine defends the truth of his narrative while admitting to his incredulous readers his inability to offer an exact picture of his past life, by looking at his views on memory, language and cognition, as presented mainly in the last non-narrative books of this work.